2006
DOI: 10.1007/s11252-006-0016-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among nutrients, chloride and biological indices in urban Maryland streams

Abstract: Using a spatially extensive urban database constructed from the Maryland Biological Stream Survey (MBSS), we describe the relationships of nutrients in small-order streams to eight defined categories of percent catchment urbanization, correlations between chloride and conductivity in urban streams, and relationships between nutrients and chloride with two Maryland-specific indices of biotic integrity for benthic macroinvertebrates and fish assemblages. Stream nutrients become elevated with increasing percent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 45 publications
4
22
2
Order By: Relevance
“…The preponderance of evidence linking physical alterations to stream channels with urbanization in previous studies (Herlihy et al 1998;Paul and Meyer 2001;Walters et al 2003;Chadwick et al 2006;Stranko et al 2008) suggests a potential pattern of habitat alteration with urban development, although causal mechanisms cannot be determined from the present analyses. Urban development has been linked to alterations in water chemistry in Maryland (Morgan et al 2007;Walsh et al 2005), and is again supported here with the positive correlations of sulfate, chloride, and conductivity with NMS axis 2 in the direction of the urbanization vector (Table 3). Elevated sulfate and chloride concentrations may be linked to industrial and municipal waste as well as road salting in these more urban developed areas (Eisen and Anderson 1979;Kaushal et al 2005).…”
Section: Discussionsupporting
confidence: 67%
“…The preponderance of evidence linking physical alterations to stream channels with urbanization in previous studies (Herlihy et al 1998;Paul and Meyer 2001;Walters et al 2003;Chadwick et al 2006;Stranko et al 2008) suggests a potential pattern of habitat alteration with urban development, although causal mechanisms cannot be determined from the present analyses. Urban development has been linked to alterations in water chemistry in Maryland (Morgan et al 2007;Walsh et al 2005), and is again supported here with the positive correlations of sulfate, chloride, and conductivity with NMS axis 2 in the direction of the urbanization vector (Table 3). Elevated sulfate and chloride concentrations may be linked to industrial and municipal waste as well as road salting in these more urban developed areas (Eisen and Anderson 1979;Kaushal et al 2005).…”
Section: Discussionsupporting
confidence: 67%
“…It is likely that stratification of salt in deeper ponds could pose a higher risk of toxicity than we were able to represent with our sampling technique. Morgan et al (2007) showed a clear correlation between conductivity and Cl -in urban streams in Maryland, and they report that increased measures of conductivity in urban streams are largely driven by input of Cl -from road salt practices. We describe a similar relationship for stormwater management ponds.…”
Section: Discussionmentioning
confidence: 98%
“…Conductivity is often used as a measure of urbanization among freshwater systems (Morgan et al 2007). In order to identify if conductivity increases are mostly driven by the application of salts to roads that are flushed into stormwater pond receiving waters, we considered the relationship between conductivity and Cl -concentrations using a linear regression model.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Because of the great number and importance of ecosystems and social services that rivers provide, they are subject to increasing exploitation and degradation. In recent centuries, an increasing amount of floodplain areas have been developed and utilized for agriculture, aquiculture and the development of cities and towns (Jones et al, 1999;Lytle and Merritt, 2004;Morgan et al, 2007). This has significantly changed the scale and pattern of ecological land use of river systems with an importance in safeguarding critical ecological processes and providing critical ecosystem services.…”
Section: Introductionmentioning
confidence: 99%